Up-Regulation of Renin-Angiotensin System in Diabetes and Hypertension: Implications on the Development of Diabetic Nephropathy - Casarini, Dulce Elena; Arita, Danielle Yuri; Cunha, Tatiana Sousa; Ronchi, Fernanda Aparecida; Aragão, Danielle Sanches; Rosa, Rodolfo Mattar; Bertoncello, Nadia Sousa Cunha; Marcondes, Fernanda Klein (IntechOpen, 2012)
None